2018
DOI: 10.1155/2018/2983052
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Behavior of Confined Cement‐Stabilized Rammed Earth Walls

Abstract: Rammed earth is widely utilized in both developed and developing countries due to its low embodied energy and good natural moisture buffering of indoor environments. However, its application in seismic active regions was limited owing to its intrinsically low resistance to dynamic actions. is paper presents the test results of four cement-stabilized rammed earth walls with confining tie-column elements under cyclic loading, aiming at assessing the cyclic behavior of proposed rammed earth walls with confining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[8] The density of rammed earth depends on the distribution of small particles, humidity during compaction, and pressure magnitude. Keable et al [9] noted that soil tends to stick to the frame-work if compressed to the optimum limit and thus recommended using a lower humidity than values reported in the literature. The density ranges of modern and ancient rammed earth structures are 1700-2200 kg/m3 and 1770-1990 kg/m3, respectively.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…[8] The density of rammed earth depends on the distribution of small particles, humidity during compaction, and pressure magnitude. Keable et al [9] noted that soil tends to stick to the frame-work if compressed to the optimum limit and thus recommended using a lower humidity than values reported in the literature. The density ranges of modern and ancient rammed earth structures are 1700-2200 kg/m3 and 1770-1990 kg/m3, respectively.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…The cyclic charging technic has been widely used by many researchers and on various materials. A good number of works ( [7] [8] [9]) for example were carried out to understand the behavior under the cyclic charge of reinforced concrete or not. Concerning the bamboo species Oxytenantera abyssinica and Bambusa vulgaris, the work of Fozao et al [10] carried out on these species has shown that the degradation phenomena generated during cyclic loading in the plastic domain can be modeled by endochronic theory.…”
Section: Introductionmentioning
confidence: 99%